2-Hydroxy-11-methyl-16-[(E)-4-methylbenzylidene]-13-(4-methylphenyl)-1,11-diazapentacyclo[12.3.1.02,10.03,8.010,14]octadeca-3(8),4,6-triene-9,15-dione - Raju Suresh Kumar; Hasnah Osman; Mohamed Ashraf Ali; Chin Sing Yeap; Hoong-Kun Fun (Acta Crystallographica Section E, 2010)
In the title compound, C32H30N2O3, the piperidin-4-one and the two fused pyrrolidine rings adopt envelope conformations. The two methylphenyl rings are oriented at dihedral angle of 20.36 (7) and 56.24 (7)°, respectively, with respect to the indanone ring system. In the crystal structure, intermolecular O—H...N and C—H...O hydrogen bonds link the molecules into chains propagating along [001]. Weak C—H...π interactions are also observed.